Psychometrics of the Physical Resilience Scale in Older Adults Living with Dementia: Proxy Responses. (June 2023) - Resnick, Barbara; Boltz, Marie; Galik, Elizabeth; Kuzmik, Ashley; Ellis, Jeanette; Wells, Chris
Objectives: The purpose of this study was to determine if proxies can complete the Physical Resilience Scale for older adults living with dementia.Methods: This was a descriptive study using Rasch analysis and baseline data from the Function Focused Care for Acute Care Using the Evidence Integration Triangle trial. The first 240 patients living with dementia were included in this analysis.Results: There was evidence of reliability based on person and item separation index. There was no evidence of Differential Item Functioning (DIF) between genders and a DIF by race on Item 7. Validity was supported based on items fitting the model with the exception of one item, and a significant relationship between physical resilience and pain and function.Discussion: There is some evidence that the Physical Resilience Scale is reliable and valid when completed by proxy reports. Future use should remove one of the items due to redundancy.